PARADIGMA PERADILAN TATA USAHA NEGARA PASCA PERUBAHAN UNDANG-UNDANG NOMOR 5 TAHUN 1986 TENTANG PERADILAN TATA USAHA NEGARA - Rohim, Akhmad; Dirksen, A. A. Ngr. Gede (Kertha Negara : Journal Ilmu Hukum, 2013)
In writing scientific papers, entitled "Paradigm State Administrative Post Amendment Law No. 5/1986 on the State Administrative Court”, the author uses normative research methods . Law No. 5/1985 on the State Administrative Court is a court of law in the event the State Administration. Law No. 5/1986 has been amended by Law No. 9/2009 and Law No. 51/2009. Because of these changes then there is a change in the proceedings in the Administrative Court and the change has constraints in its application. In connection with the judicial procedure of Law No. 5/1986 experienced a change in the reason of filing a lawsuit and implementation of the Administrative Decisions Tribunal. Faced obstacles encountered in the implementation of changes to the Law No. 5 /1986 are at the level of understanding of the law and society.
Keywords: Proceeding Law, Administrative court, Paradigm